Phase III Trial of Standard-Dose Intravenous Cisplatin Plus Paclitaxel Versus Moderately High-Dose Carboplatin Followed by Intravenous Paclitaxel and Intraperitoneal Cisplatin in Small-Volume Stage III Ovarian Carcinoma: An Intergroup Study of the Gynecologic Oncology Group, Southwestern Oncology Group, and Eastern Cooperative Oncology Group - Markman, Maurie; Bundy, Brian N.; Alberts, David S.; Fowler, Jeffrey M.; Clark-Pearson, Daniel L.; Carson, Linda F.; Wadler, Scott; Sickel, Joshua (Journal of clinical oncology, 2001)
PURPOSE: To compare the progression-free and overall survival in small-volume residual ovarian cancer after treatment with intravenous (IV) cisplatin and paclitaxel or an experimental regimen of IV carboplatin followed by IV paclitaxel and intraperitoneal cisplatin. PATIENTS AND METHODS: Patients were randomized to receive either IV paclitaxel 135 mg/m 2 over 24 hours followed by IV cisplatin 75 mg/m 2 every 3 weeks for six courses or IV carboplatin (area under curve 9) every 28 days for two courses, then IV paclitaxel 135 mg/m 2 over 24 hours followed by intraperitoneal (IP) cisplatin 100 mg/m 2 every 3 weeks for six courses. RESULTS: Of the 523 patients who entered this trial, 462 were determined to be assessable, with prognostic factors well balanced between the treatments. Neutropenia, thrombocytopenia, and gastrointestinal and metabolic toxicities were greater in the experimental arm. As a result, 18% of the patients received ≤ two courses of IP therapy. Progression-free survival was superior for patients randomized to the experimental treatment arm (median, 28 v 22 months; relative risk, 0.78; log-rank P = .01, one-tail). There was a borderline improvement in overall survival associated with this regimen (median, 63 v 52 months; relative risk, 0.81; P = .05, one-tail). CONCLUSION: An experimental regimen including moderately high-dose IV carboplatin followed by IP paclitaxel and IV cisplatin yielded a significant improvement in progression-free survival when compared with a standard regimen of IV cisplatin and paclitaxel. Because the improvement in overall survival was of borderline statistical significance and toxicity was greater, the experimental arm is not recommended for routine use. However, the results provide direction for further clinical investigation in small-volume ovarian cancer.